2014
DOI: 10.1016/j.concog.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Question format shifts bias away from the emphasised response in tests of recognition memory

Abstract: The question asked to interrogate memory has potential to influence response bias at retrieval, yet has not been systematically investigated. According to framing effects in the field of eyewitness testimony, retrieval cueing effects in cognitive psychology and the acquiescence bias in questionnaire responding, the question should establish a confirmatory bias. Conversely, according to findings from the rewarded decision-making literature involving mixed incentives, the question should establish a disconfirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The d’ calculation was adjusted for instances of zero false alarms (Snodgrass and Corwin, 1988; Mill and O’Connor, 2014). JoAs and JoPs were quantified as a percentage of the VAS scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The d’ calculation was adjusted for instances of zero false alarms (Snodgrass and Corwin, 1988; Mill and O’Connor, 2014). JoAs and JoPs were quantified as a percentage of the VAS scale.…”
Section: Methodsmentioning
confidence: 99%
“…To characterize participants’ strategies, the response bias ( c ) measure from signal detection theory (Green and Swets, 1966) was used, with a correction for zero false alarms (Snodgrass and Corwin, 1988; Mill and O’Connor, 2014). Zero reflects an unbiased criterion, negative values reflect a liberal criterion, and positive values denote a conservative criterion.…”
Section: Methodsmentioning
confidence: 99%
“…This is a dummy question to check the consistency of the respondents' attitude in answering the questions. 7,8) Therefore, we decided not to include the results of this particular question in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…fluency of processing) in determining whether an item is familiar [ 22 ] or whether they are in a subjective mnemonic state such as TOT [ 21 ] and that people might experience a degree of uncertainty as to what exactly they are experiencing [ 23 ]. Additionally, a large body of literature has demonstrated that the way a question is framed can bias memory reports in eye-witness situations [ 24 ], and classic memory [ 6 ] and metamemory [ 25 ] tasks. If a participant is unsure of what she is experiencing and interprets being asked about experiencing déjà vu or TOT as indicative that she should be experiencing déjà vu or TOT, she may reinterpret her current state as that which she is asked about.…”
Section: Discussionmentioning
confidence: 99%
“…One worry is that self-reports are unreliable, and therefore contribute to results which are limited in their capacity to inform theories of subjective experiences and their prevalence. Experimental participants are not merely passive respondents; they are often motivated to confirm what they perceive as the experimental hypothesis [ 5 ] and try to be relevant by focusing their reports on what they believe the experimenter is interested in [ 6 , 7 ]. This is likely true for any experiment but it has also been suggested it might be a fundamental problem for research on subjective mnemonic experiences as a result of limitations in current methods [ 2 ].…”
Section: Introductionmentioning
confidence: 99%